2007
DOI: 10.1016/s0210-4806(07)73657-4
|View full text |Cite
|
Sign up to set email alerts
|

Presentación de un nuevo caso de adenocarcinoma de células claras uretral y su manejo quirúrgico

Abstract: It is an unusual type of cancer associated with poor prognosis. Currently the construction of a continent urinary diversion using the Mitrofanoff principle has many indications as our case. Laparoscopic radical cystectomy can be done by experienced groups without adding much more technical difficulties; there are no long-term oncological outcome data but we believe in some functional advantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
(6 reference statements)
2
2
0
Order By: Relevance
“… Zaviačič and associates [ 18 ] had reported a neoplasm with similar histological appearance and immunohistochemical features as adenocarcinoma of Skene's paraurethral gland and ducts. Their aforementioned findings would support the postulate of Abascal Junquera and associates [ 11 ] that the female clear cell adenocarcinoma arises from the paraurethral duct. Nevertheless, it would seem that female urethral adenocarcinoma has more than one tissue of origin with minority arising from the Skene's glands as suggested by Dodson and associates [ 19 ].…”
Section: Literature Reviewsupporting
confidence: 79%
See 2 more Smart Citations
“… Zaviačič and associates [ 18 ] had reported a neoplasm with similar histological appearance and immunohistochemical features as adenocarcinoma of Skene's paraurethral gland and ducts. Their aforementioned findings would support the postulate of Abascal Junquera and associates [ 11 ] that the female clear cell adenocarcinoma arises from the paraurethral duct. Nevertheless, it would seem that female urethral adenocarcinoma has more than one tissue of origin with minority arising from the Skene's glands as suggested by Dodson and associates [ 19 ].…”
Section: Literature Reviewsupporting
confidence: 79%
“…Their aforementioned findings would support the postulate of Abascal Junquera and associates [ 11 ] that the female clear cell adenocarcinoma arises from the paraurethral duct. Nevertheless, it would seem that female urethral adenocarcinoma has more than one tissue of origin with minority arising from the Skene's glands as suggested by Dodson and associates [ 19 ].…”
Section: Literature Reviewsupporting
confidence: 79%
See 1 more Smart Citation
“…With the development of laparoscopic equipment, laparoscopic radical cystectomy with urinary diversion has become feasible and provides many intraoperative and postoperative advantages over the traditional open approach [9]. A review of the literature found only one reported case of the laparoscopic approach in patients with a urethral tumor [9]. However, laparoscopic surgery in this setting of adenocarcinoma arising from the urethral diverticulum has not previously been reported in the English literature.…”
Section: Discussionmentioning
confidence: 99%